Integrated Web-Based System of Student Admission and Donations - Myrna Dwi Rahmatya; Zahra Rizqia Aswin; Muhammad Dafa Ikhlashul Amal; Dian Permata Sari; Mochamad Fajar Wicaksono; Leonardi Paris Hasugian (2025)
Abstract - Digital transformation in school administration is essential to improve efficiency and transparency. SMPIT Mutiara still relies on manual procedures for student admission, tuition payment, and donation management, which often cause delays and data loss. This research aims to develop a web-based information system to support these administrative processes. The methodology applies an object-oriented approach using Unified Modeling Language (UML) and the prototyping development model. The research stages include requirements analysis, system design, prototype building, user evaluation, and refinement. The results indicate that the developed system successfully integrates student admission, selection, re-registration, tuition payment, and donation management workflows. It also generates automated reports that assist in monitoring and decision-making. In conclusion, the system is effective in reducing errors, accelerating administrative processes, and enhancing financial transparency. For future development, the system may be extended to academic modules such as student assessment and attendance tracking.Keywords: Web-Based Information System; Student Admission; Tuition Payment; Donation Management; Prototyping Model; Abstrak - Transformasi digital dalam administrasi sekolah menjadi kebutuhan penting untuk meningkatkan efisiensi dan transparansi. SMPIT Mutiara masih menggunakan prosedur manual dalam pendaftaran siswa baru, pembayaran SPP, dan pengelolaan dana donasi, yang menimbulkan keterlambatan serta potensi kehilangan data. Penelitian ini bertujuan mengembangkan sistem informasi berbasis web untuk mendukung proses administrasi tersebut. Metode yang digunakan adalah pendekatan berorientasi objek dengan Unified Modeling Language (UML) dan model pengembangan prototyping. Proses penelitian meliputi analisis kebutuhan, perancangan sistem, pembangunan prototipe, evaluasi pengguna, dan penyempurnaan sistem. Hasil penelitian menunjukkan bahwa sistem yang dibangun mampu mengintegrasikan alur pendaftaran siswa, seleksi, pendaftaran ulang, pembayaran SPP, serta pengelolaan donasi. Sistem ini juga menghasilkan laporan otomatis yang dapat digunakan untuk monitoring dan pengambilan keputusan. Kesimpulannya, sistem ini efektif dalam mengurangi kesalahan, mempercepat proses administrasi, dan meningkatkan transparansi keuangan. Untuk pengembangan selanjutnya, sistem dapat diperluas ke modul akademik seperti penilaian dan absensi.Kata kunci: Sistem Informasi Berbasis Web; Penerimaan Siswa Baru; Pembayaran SPP; Pengelolaan Donasi; Model Prototyping;